Trends in oral cancer rates in the United States, 1973–1996 - Shiboski CH, Shiboski SC, Silverman S Jr (Blackwell Synergy, 2000)
To explore changes in demographic distribution, incidence and survival rates of oral cancer in the United States from 1973 through 1996. Methods: From the Surveillance, Epidemiology, and End Results (SEER) data, we computed the proportion of oral cancer by demographic characteristics, site, and stage at diagnosis for 1973–84 and 1985–96. We estimated incidence and 5-year relative survival rates of oral cancer by age, gender, and race/ethnicity, and compared survival rates between the two periods. The estimated annual percent change (EAPC) was used to explore trends in incidence rate from 1973 through 1996.